Cost Minimization Techniques: A Case of Dairy Product Manufacturers in Pakistan - Billah, Usamah Iyyaz (Information Management and Business Review, 2013)
One of the key challenges faced by manufacturing concerns in Pakistan is maintaining (or preferably increasing) the profitability level of their operations. For the purpose of this descriptive study, the dairy sector of Pakistan has been selected as a sample industry. The literature review explains why the dairy sector has been selected for this research, the key cost components and why cost minimization is necessary for companies manufacturing dairy products in Pakistan. A primary survey has been conducted with managers in top dairy companies of Pakistan and the findings have been discussed in detail. The findings include identification of cost components and their impact, cost minimization techniques and their impact on profitability as well as suggestions for new cost reduction measures. This research article is the first one conducted on this topic in Pakistan and can also open new avenues for further research in this area.